2015
DOI: 10.1378/chest.14-0914
|View full text |Cite
|
Sign up to set email alerts
|

Health Literacy, Cognitive Function, Proper Use, and Adherence to Inhaled Asthma Controller Medications Among Older Adults With Asthma

Abstract: Among older patients with asthma, interventions to promote proper medication use should simplify tasks and patient roles to overcome cognitive load and suboptimal performance in self-care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
59
2
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(71 citation statements)
references
References 44 publications
(57 reference statements)
4
59
2
2
Order By: Relevance
“…The ability of patients and caregivers to properly coordinate the actuation and inhalation required with some inhalers (e.g., metered-dose inhalers) may limit the effectiveness of the medication (9)(10)(11)(12). A novel, inhalation-driven, multidose dry powder inhaler (MDPI; Teva Pharmaceutical Industries, Frazer, PA, USA) was developed that is intuitive and simple for patients to use (13).…”
Section: Introductionmentioning
confidence: 99%
“…The ability of patients and caregivers to properly coordinate the actuation and inhalation required with some inhalers (e.g., metered-dose inhalers) may limit the effectiveness of the medication (9)(10)(11)(12). A novel, inhalation-driven, multidose dry powder inhaler (MDPI; Teva Pharmaceutical Industries, Frazer, PA, USA) was developed that is intuitive and simple for patients to use (13).…”
Section: Introductionmentioning
confidence: 99%
“…To assess adherence to medication, one of the instruments used were the Medication Adherence Reporting Scale for Asthma (MARS-A) (26) . This tool is a measure of 10 items, validated, which was adapted to verify self-report of adherence to inhaled corticosteroids, which goes according to the objectives of the studies surveyed, related to asthma (22)(23) . It can be a tool used by nurses to aid in research or clinical practice in asthma.…”
Section: Discussionmentioning
confidence: 99%
“…The fifth article states that the FHL is directly related to inaccurate beliefs about medicines for asthma, influencing the non-adherence to medication (21) . Finally, the sixth (22) and seventh articles found that individuals with inadequate FHL have low adherence to medication and worst self-care for asthma (23) . As for the strategies and interventions related to adherence and to the FHL, the following results were obtained: first, it was brought the importance of education, communication and patient guidance, in addition to the use of methods more suitable in interventions, such as using proper language, simplifying reading materials and adapting care as needed and resources of each individual (19)(20)(21)(22)(23) .…”
Section: Prospective Cohortmentioning
confidence: 99%
See 1 more Smart Citation
“…The improper use of inhaler devices, such as MDIs and conventional DPIs, is a common problem [8,9] that may significantly limit the effectiveness of these devices [8,[10][11][12]. A novel inhalation-driven device (multidose dry powder inhaler [MDPI]; Teva Pharmaceuticals, Inc., Frazer, PA) has been developed that uses a cyclone design that facilitates efficient de-agglomeration and aerosolization of the drug particles from the lactose carrier.…”
Section: Introductionmentioning
confidence: 99%